Vector Fields on the Space of Functions Univalent Inside the Unit Disk via Faber Polynomials - Airault, H. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
We obtain the Kirillov vector fields on the set of functions f univalent inside the unit disk, in terms of the Faber polynomials of 1/f(1/z). Our construction relies on the generating function for Faber polynomials.